Two degrees up—Part Three: Kenya - Jarvis, Andy (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
A look at farming systems in the country's Mount Kenya region, and innovative ways for small farmers to adapt to the problem of water stress, compounded by rising temperatures and unpredictable rain. Part of the Two Degrees Up series to mark the launch of the CGIAR's Climate Change, Agriculture and Food Security Research Program (CCAFS), led by the International Center for Tropical Agriculture (CIAT), to develop scientific solutions to help small farmers around the world adapt to climate change.